Bacterial contamination on beef carcass at selected abattoirs located in Selangor, Malaysia - Chong, Elizabeth Sinirisan; Zul Fadhli Bidin,; Nur Faizah Abu Bakar,; Siti Shahara Zulfakar, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The ruminant industry is one of the most burgeoning sectors in Malaysia. With increasing beef productions in Malaysia, the issue of bacterial contamination on beef carcass deserves extra attention as to ensure public food safety. The main objective of this study was to determine the level of bacterial contamination of beef carcasses by determining the presence of selected microorganisms (total plate count, Enterobacteriaceae, Escherichia coli and Salmonella spp.). Swab samples were taken from the two abattoirs located in Selangor, Malaysia from October 2015 to February 2016. The results obtained showed that the samples (n = 40) of the two abattoirs has recorded an average reading of 4.00 ± 0.934 log CFU/cm2 for total plate count. Enterobacteriaceae was detected from 82.5% of total samples with an average reading of 2.728 ± 0.936 log CFU/cm2. While for E. coli was isolated from 55% of total samples with an average reading of 1.87 log CFU/cm2. A total of 4 samples (10%) were tested positive for the presence of Salmonella spp. The result reflect on the level of contamination of locally produced beef in Malaysian abattoirs. Thus, this study will allow better interventions from related authorities in order to improve the safety and the quality of locally produced beef.